Response of yield and quality of Japonica rice to different gradients of moisture deficit at grain-filling stage in cold regions - Fan Mingyu; Lin Tian; Sun Shixin; Hou Miao; Yang Chuanming; Hu Congcong; Li Hongyu; Zheng Guiping (Open Chemistry, 2024)
Water stress significantly affects on rice yield and quality. Eight Japonica varieties from the first and second accumulated temperature zones of Heilongjiang Province were used as materials and four moisture gradients (0, −10, −25 and −40 kPa) were conducted at the grain-filling stage to clarify the effect of water stress on the rice yield and quality in cold regions. The results showed that the rice yield was reduced due to the decrease in the seed setting rate. Rice chalkiness was significantly increased by drought stress, especially under −10 kPa. The protein content of most varieties was significantly reduced and taste quality was increased under −25 to −40 kPa. The effect on protein components increased with increasing drought stress. The gel consistency decreased and the average chain length of amylopectin was less affected by drought. With an increase in moisture deficit, the rapid viscosity analyzer characteristics and chain length distribution of amylopectin showed a trend of first increasing and then decreasing or decreasing and then increasing. The response of starch to mild and severe drought varied. Our study provides a theoretical basis for the efficient utilization of water and high quality and yield of Japonica rice.